Evaluation of pattern ERG as a visual prognosticator in chiasmatic tumours. (16th July 2013) - Goyal, Jawahar L; Thangkhiew, Lanalyn; Yadava, Usha; Arora, Ritu; Jain, Parul
Abstract Background Tumours compressing the optic pathway may lead to irreversible loss of vision that can be detected by pattern electroretinogram owing to its relation to ganglion cell function. This study aims to assess whether pattern electroretinogram is a useful tool to predict visual outcome following decompressive surgery for sellar and parasellar tumours. Design Prospective, non‐randomized study. Participants Forty eyes of 20 patients with radiologically confirmed tumours in and around the sellar region. Methods Patients were followed for 6 weeks following surgical intervention (transphenoidal or transfrontal approach). Main Outcome Measures Best‐corrected visual acuity, visual fields (Humphrey 30‐2 standard automated perimetry) and pattern electroretinogram. The ratio N95/P50 (N2/P1) was calculated for each recording. Results There was improvement in visual fields in 35.4% eyes with normal n2/p1 ratio (>1.1) as compared to 22.2% with abnormal ratio. Also, 9.6% eyes with normal ratio and 11.1% with an abnormal ratio deteriorated postoperatively. No association was found between pattern electroretinogram and visual fields preoperatively and postoperatively (P = 0.093). Conclusions Pattern electroretinogram may not be a useful prognostic indicator in the preoperative assessment of tumours causing chiasmal compression. An abnormal N2/P1 ratio is not necessarily associated with lesser or no clinical improvement following surgery as compared to an eye with a normal pattern electroretinogram.